2022
DOI: 10.21203/rs.3.rs-1420033/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translocator protein is a marker of activated microglia in rodent models but not human neurodegenerative diseases

Abstract: Microglial activation plays central roles in neuro-inflammatory and neurodegenerative diseases. Positron emission tomography (PET) targeting 18kDa Translocator Protein (TSPO) is widely used for localising inflammation in vivo, but its quantitative interpretation remains uncertain. For the first time, we show that TSPO gene and protein expression increases in activated microglia in mouse brain disease models postmortem, but does not change in a non-human primate (Callithrix jacchus) disease model or in common n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 77 publications
1
16
1
Order By: Relevance
“…This is not surprising, considering that plasma GFAP is expected to reflect more astrocytic reactivity associated with Aβ pathology, 39 whereas TSPO PET is thought to reflect microglial density. 20 Our results with GFAP support the previous findings suggesting that reactive astrocytosis is present already in cognitively normal individuals and related to Aβ pathology. 37, 39, 63…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is not surprising, considering that plasma GFAP is expected to reflect more astrocytic reactivity associated with Aβ pathology, 39 whereas TSPO PET is thought to reflect microglial density. 20 Our results with GFAP support the previous findings suggesting that reactive astrocytosis is present already in cognitively normal individuals and related to Aβ pathology. 37, 39, 63…”
Section: Discussionsupporting
confidence: 91%
“…TSPO is present in the outer mitochondrial membranes of microglia and elevated in the brain in relation to injuries or pathology 19 . In humans, increased TSPO ligand-binding has recently been suggested to represent changes in cell density rather than protein overexpression 20 , and to be mostly covered by microglia, and to a lesser extent astrocytes and endothelial cells 21, 22 . Previous studies using TSPO PET imaging have shown increased regional ligand-binding in patients with Alzheimer’s disease 23-26 , mild cognitive impairment 4, 27, 28 and in Aβ-positive compared with -negative controls 7, 29 .…”
Section: Introductionmentioning
confidence: 99%
“…For many years, TSPO was thought to be specific to microglial activation, yet TSPO can also be bound by other inflammatory cells, including astrocytes and peripheral immune cells 73-76 . More recent studies in rodent models have suggested that TSPO signal may be related more to microglial number than microglial activation 77 . While our observations suggest that increased TSPO signal reflects central inflammation and correlates with cognitive measures, the TSPO signal we observed is found in multiple brain regions and does not offer clear insight into the cell types that may be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, TSPO PET was found to reflect the density of inflammatory cells rather than their activation in humans, because its expression in human myeloid cells is related to different phenomena. Therefore, TSPO PET can reflect activated microglia in rodents but not in humans, which means the interpretation of TSPO PET data requires revision [19]. Therefore, more neuroimmune imaging biomarkers are necessary to overcome the limitation of TSPO PET.…”
Section: Brief Introduction Of Neuroinflammation and Associated Tracersmentioning
confidence: 99%